PENGARUH KESEHATAN DAN KESELAMATAN KERJA TERHADAP PRODUKTIVITAS KERJA PT EPSON BATAM - Mulrisya, Mely; Raymond (LPPM Universitas Putera Batam, 2021)
It is important to pay attention to occupational health and safety because in the production area there are many chemicals that wiII be harmfuI to the heaIth and safety of empIoyees if inhaled or exposed to body parts. The purpose of this study was to determine whether occupationaI safety, heaIth, affect the work productivity of PT Epson Batam. The number of sampIes was determined using the SIovin formula and the number of sampIes in this study were 353 consumers. The sampIing technique used was random sampIing. Testing the effect in this study using muItipIe Iinear anaIysis and coefficient and determination anaIysis (R2), hypothesis testing using T test and F test using SPSS version 25 software program. The resuIts show that the variables of occupational safety, health partiaIIy and simuItaneously have a signiificant effect on productivity. working at PT Epson Batam